Blogger phobia: lecturers' apprehension towards the use of slogs in ESL teaching and learning - Noor Azlinda, Zainal Abidin; Ezihaslinda, Ngah; Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan (2009)
To keep up with rapid technology advancement in the field of teaching and learning, a technical university in Malaysia, Universiti Malaysia Pahang (UMP) with its tagline, 'Engineering, Technology, Creativity', has introduced the use of blogs in one of the English courses taken by all its engineering undergraduates, offered by the Center for Modern Languages and Human Sciences (CMLHS). The blogs are served as platforms for these undergraduates to share their experience learning English as a second language (ESL) with their learning peers. As blogging is slowly placing itself in a comfortable position among blog savvy, some of the CMLHS language instructors have never blogged. This paper sought to get response and feedback on the introduction and implementation ofblogging in ESL classrooms from all language instructors involved through distribution of a set of questionnaire. The findings of this study show positive responses on blog incorporation and the feedback is used to improve the blog implementation in other English courses.